Whole genome SNP genotyping in a family segregating developmental dysplasia of the hip detected runs of homozygosity on chromosomes 15q13.3 and 19p13.2. (29th August 2017) - Basit, Sulman; Alharby, Essa; Albalawi, Alia M.; Khoshhal, Khalid I.
Abstract: Developmental dysplasia of the hip (DDH) is one of the most prevalent developmental orthopedic diseases worldwide. DDH is a spectrum of anatomical abnormalities of the hip joint and is characterized by premature arthritis in later life. Sporadic cases have been reported more frequently; however, some studies have reported families segregating DDH. Studies have suggested that the genetic factors play a significant role in the development of DDH. In order to detect genetic defect underlying DDH, we performed Sanger sequencing of all DDH associated genes, whole genome SNP genotyping and exome sequencing in a Saudi family with four individuals having DDH. Sanger sequencing of all known genes did not identify any pathogenic variant. Genotype data analysis using HomozygosityMapper identified shared homozygous regions on chromosome 15q13.3 and chromosome 19p13.2 flanked by rs17228178‐rs1534200 and rs466123‐rs2112461, respectively. These data were also analyzed by cnvpartition software for identification of DDH associated copy number variations (CNV). A shared copy number gain of approximately 15 kb on chr6p21.32 (chr6:33 053 906–33 069 893) was discovered in all affected individuals. Partial gain of this region has also been found in unaffected sibling of this family. Exome data did not reveal any candidate sequence variant. Whole genome sequencing is required to identify deep intronic variants in the shared homozygous regions. Identification of genetic variants involved in pathogenesis of DDH may open up interesting perspectives into the function of the gene(s) in hip joint development.